2016
DOI: 10.18632/oncotarget.11450
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate induced epithelial-mesenchymal transition of hepatocellular carcinoma via an MMP-7/syndecan-1/TGF-β autocrine loop

Abstract: Sphingosine-1-phosphate (S1P) induces epithelial–mesenchymal transition (EMT) in hepatocellular carcinoma (HCC). However, its underlying mechanism remains largely unknown. In the present study, we investigated the correlation between S1P and syndecan-1 in HCC, the molecular mechanism involved, as well as their roles in EMT of HCC. Results revealed a high serum S1P level presents in patients with HCC, which positively correlated with the serum syndecan-1 level. A significant inverse correlation existed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 45 publications
5
85
0
1
Order By: Relevance
“…We also show that expression of SPHK1 correlates significantly with EMT score in breast cancer, consistent with previous studies that also suggest its involvement in EMT (26,57,58).…”
Section: Discussionsupporting
confidence: 92%
“…We also show that expression of SPHK1 correlates significantly with EMT score in breast cancer, consistent with previous studies that also suggest its involvement in EMT (26,57,58).…”
Section: Discussionsupporting
confidence: 92%
“…Though S1P’s role in cancer is multifaceted, the cancer field has mainly explored roles for cer-amide signaling and an inflammatory response; we suggest that dysregulated cell extrusion should also be considered, especially considering the elegant report demonstrating the S1P receptor’s key role in cancer cell extrusion and metastasis (Gu et al, 2015). Intriguingly, S1P is reported to trigger EMT in certain human hepatocellular carcinoma (Zeng et al, 2016) and lung cancer lines (Milara et al, 2012), and S1P was upregulated in patients with idiopathic pulmonary fibrosis, a disease characterized by frequent EMT (Milara et al, 2012); this further hints at the possibility of extrusion-EMT coupling in cancer. Last, Piezo1, the master regulator of live cell extrusion, is mutated or misex-pressed in colorectal, gastric, and thyroid cancers (Gudipaty et al, 2017), and Piezo1 promoted the invasion of gastric cancer cells in vitro (Yang et al, 2014).…”
Section: A Force For Evil: Cell Extrusion In Diseasementioning
confidence: 99%
“…Numerous studies have shown that CCAT1 acts as an oncogene, and is highly expressed in many malignancies, such as colorectal, gastric, ovarian, breast, gallbladder, hepatocellular carcinoma, and lung cancer (Cao et al, ; Gao et al, ; Jia et al, ; Li et al, ; Zhang et al, ; Zhang and Hu, ). CCAT1 exerts its carcinogenic effect by promoting cell invasion and metastasis (Zhao et al, ) and this has been widely studied (Zeng et al, ). Several recent studies suggest that CCAT1 serves as a biomarker for the prognosis of tumors and its expression is often associated with poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%